2013
DOI: 10.1111/sjop.12041
|View full text |Cite
|
Sign up to set email alerts
|

School context and health in adolescence: The role of sense of coherence

Abstract: The aim of this study was to examine the role of school variables and sense of coherence (SOC) in the explanation of health. For this purpose, data were collected from a representative sample of adolescents, aged 13 to 18 years, selected for the Health Behavior in School-aged Children survey in Spain. Using Structural Equation Modelling, three nested models were tested that represented different hypothesized models of the relationships among school factors, SOC and health. According to goodness-of-fit indices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
3
42
1
4
Order By: Relevance
“…Previous studies have confirmed the existence of association between SOC and the general health status of individuals [28,29], including the oral health of infants [11], adolescents [12] and adults [13]. These studies are in agreement with the salutogenic theory, in which the higher / stronger the SOC, the healthier the individuals [5].…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have confirmed the existence of association between SOC and the general health status of individuals [28,29], including the oral health of infants [11], adolescents [12] and adults [13]. These studies are in agreement with the salutogenic theory, in which the higher / stronger the SOC, the healthier the individuals [5].…”
Section: Discussionsupporting
confidence: 79%
“…Esta experiencia va siempre acompañada de múltiples y significativos cambios y retos en las áreas académica, social y emocional. Estas circunstancias de cambio pueden derivar en el desarrollo de reacciones de estrés (Bíro, Ádány y Kósa, 2011;García-Moya, Rivera y Moreno, 2013;Grevenstein, Bluemke, Nagy, Wippermann y Kroeninger-Jungaberle, 2014). Estos investigadores coinciden en la importancia de valorar a los estudiantes como una población de estudio de las más relevantes.…”
Section: Introductionunclassified
“…For example, analyses of the HBSC study have shown that high-SOC adolescents seemed to be less prone to perceive school life as stressful (García-Moya et al, 2013d;Torsheim et al, 2001). This mirrors evidence from the adult literature which demonstrated that high-SOC adults tended to report a lower number of negative life events (Volanen et al, 2007).…”
Section: Salutogenesis and Explanationmentioning
confidence: 99%
“…Relationships with parents (Feldt et al, 2005;García-Moya et al, 2012), support from teachers and classmates (García-Moya et al, 2013d;Natvig et al, 2006), behavioural models in the peer group (García-Moya et al, 2013b) and neighbourhood quality (García-Moya et al, 2013a;Marsh et al,2007) have all been identified as potential precursors of SOC during adolescence.…”
Section: Salutogenesis and Explanationmentioning
confidence: 99%